2017
DOI: 10.3389/fpls.2017.00490
|View full text |Cite
|
Sign up to set email alerts
|

Rubisco and Rubisco Activase Play an Important Role in the Biochemical Limitations of Photosynthesis in Rice, Wheat, and Maize under High Temperature and Water Deficit

Abstract: To understand the effect of heat and drought on three major cereal crops, the physiological and biochemical (i.e., metabolic) factors affecting photosynthesis were examined in rice, wheat, and maize plants grown under long-term water deficit (WD), high temperature (HT) and the combination of both stresses (HT-WD). Diffusional limitations to photosynthesis prevailed under WD for the C3 species, rice and wheat. Conversely, biochemical limitations prevailed under WD for the C4 species, maize, under HT for all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
178
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(191 citation statements)
references
References 109 publications
(148 reference statements)
11
178
2
Order By: Relevance
“…Data were collected post-anthesis in glasshouse-grown plants with a Licor 6400XT mounted with a bespoke cuvette ensuring saturating light (1000 lmol m À2 sec À1 ) and a 25°C block temperature. (Scafaro et al, 2012;Scafaro et al, 2016;Perdomo et al, 2017). On the other hand, this 'risky' behaviour might increase the possibility of early ear dehydration under severe terminal stress conditions, although further experimental evidence is required to support this theory.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Data were collected post-anthesis in glasshouse-grown plants with a Licor 6400XT mounted with a bespoke cuvette ensuring saturating light (1000 lmol m À2 sec À1 ) and a 25°C block temperature. (Scafaro et al, 2012;Scafaro et al, 2016;Perdomo et al, 2017). On the other hand, this 'risky' behaviour might increase the possibility of early ear dehydration under severe terminal stress conditions, although further experimental evidence is required to support this theory.…”
Section: Resultsmentioning
confidence: 98%
“…For example, increasing stomatal density or aperture could result in increasing assimilation by removing diffusional constraints and increasing the flux of atmospheric CO 2 to the site of carboxylation; however, such an approach would also facilitate the leakage of respiratory CO 2 (Sui et al , ), which has been demonstrated to be of greater importance in some organs. Alternatively, increased stomatal density in wheat ears could improve evaporative cooling, thereby maintaining assimilation rates under elevated temperatures, assuming a similar temperature sensitivity of photosynthesis in wheat ears and leaves (Scafaro et al , ; Scafaro et al , ; Perdomo et al , ). On the other hand, this ‘risky’ behaviour might increase the possibility of early ear dehydration under severe terminal stress conditions, although further experimental evidence is required to support this theory.…”
Section: Resultsmentioning
confidence: 99%
“…which presumably enables photosynthesis to continue at higher temperatures, considering that the heat-labile nature of Rca is a major limitation on photosynthesis at higher temperatures for many plant species, including wheat (Feller et al, 1998;Crafts-Brandner and Salvucci, 2000;Sage et al, 2008;Perdomo et al, 2017;Kumar et al, 2019). The fact that other species such as cotton (Gossypium hirsutum) and maize (Zea mays; Sánchez de Jiménez et al, 1995;DeRidder and Salvucci, 2007) also induce specific isoforms of Rca in response to heat stress suggests convergent evolution of the induction of heatstable Rca isoforms in response to heat.…”
Section: Discussionmentioning
confidence: 99%
“…One of the defining characteristics of Rca is that it is a heat-labile protein and in many species dissociates, denatures, and aggregates with even moderate heat application, to a much greater extent than Rubisco (Feller et al, 1998;Salvucci et al, 2001;Salvucci and Crafts-Brandner, 2004). As such, Rca is considered one of the main causes of a decrease in photosynthetic function for plants exposed to supraoptimal temperatures (Crafts-Brandner and Salvucci, 2000;Sage et al, 2008;Busch and Sage, 2017;Perdomo et al, 2017). Improving the thermostability of Rca is therefore considered one of the most promising ways of improving photosynthesis and thus potentially the yield of crops exposed to the detrimental impacts of heat stress (Parry et al, 2011;Carmo-Silva et al, 2015).…”
mentioning
confidence: 99%
“…Images were analysed using ImageJ (Rasband, 2016) to determine band densities of each sample. The RuBisCo, RCA and its two isoforms concentration were expressed as relative to the sample representing the highest density (Perdomo et al, 2017; Prins et al, 2008; Ristic et al, 2009).…”
Section: Methodsologymentioning
confidence: 99%